The Relationship Between Family Support And The Mental Health Of Public Health Student At Manado State University - Hersilya Pingkan Ambalabi; Agustievie Telew; Jilly Toar; Deviana Munthe; Beatrix Podung; Eduard Kumenap (International Journal of Health Engineering and Technology, 2026)
Mental health is an important concern given the various academic pressures faced, especially in the final project completion phase. This study aims to analyze the relationship between family support and mental health level in Public Health Sciences students of Manado State University. This study used a Cross-Sectional design involving 60 respondents. Data were collected using questionnaires, the questionnaires used were the Family Support questionnaire and DASS-24 and analyzed using the Chi-Square test. The results showed that the majority of respondents were female (88.4%) and male (11.7%) with an age range of 21-24 years. As many as 85.0% of respondents received good family support. The results of the calculation of mental health levels showed that 31.7% experienced mild depression, 51.7% experienced very severe anxiety, and 78.3% experienced normal stress. The results of the Chi-square test showed that there was no significant relationship between family support and levels of depression (p=0.836), anxiety (p=0.244), and stress (p=0.219). The conclusion of the study was that there was no relationship between family support and the level of mental health of students of Social Health Sciences, Manado State University. This indicates that students' mental health is affected by other factors such as other social supports.